Determination of amounts of some vitamin B groups in domestic wastewater treatment plants - Selimoğlu, Fatih; Öbek, Erdal; Karataş, Fikret; Arslan, E. İşıl; Tatar, Şule Yüksel (Fırat University, 2015)
Some living species need vitamins required for matter modifications which are realized particularly through biochemical reactions, while some need a few of them or do not need any of them. The living organisms obtain those matters, which are essential for surviving, from their existing environments. Therefore, the quantity of vitamins in those environments should be identified. In this sense, the quantity of vitamins in wastewater treatment plants which are the environments of microorganisms also should be determined. In this study, the levels of B1 (Thiamin), B2 (Riboflavin), B3 (Niacin), B6 (Pyridoxine), B11 (Folic Acid) and B12 (Cobalamin) among vitamin B groups which can be dissolved in water were determined in water and treatment sludge of Malatya and Gaziantep wastewater treatment plants (Turkey). The levels of B1, B2, B3, B6, B11 and B12 in the samples obtained from Malatya and Gaziantep wastewater treatment plants were found out to be significantly different. The results are statistically significant with respect to p < 0.05 and p < 0.01. Such differences emerged depending on the characteristics of purified water and microbial characteristics. The determined vitamin levels were found out to be satisfactory for the vitamin requirements of heterotrophic microorganisms in both biological wastewater treatment and soil.